The Role of Infrastructural and Psychological Factors in Sustainable Transportation Mode Choices - Eva Gößwein; Johannes Aertker; Dirk Wittowsky; Magnus Liebherr (Applied Sciences)
Individual mobility behavior continues to pose a challenge to achieving climate goals, as motorized individual transportation is still favored over public transportation. The present study examines five possible drivers of more sustainable transportation mode choices: two infrastructural factors, specifically city center accessibility and railway accessibility, and three psychological variables: adaptability, climate change perception, and car orientation. A sample of N = 187 participants was collected in a German city in the Lower Rhine region. Our findings, based on ordinal logistic regression models, indicate that railway accessibility and car orientation are associated with both the use of motorized and public transportation. While center accessibility and adaptability predicted the use of motorized individual transportation, these variables did not significantly relate to the use of public transportation. Also, our results indicate that climate change perception does not relate to transportation use. This surprising finding is discussed in detail. On a more general level, the study’s insights reinforce previous findings and stress the importance of considering not only infrastructural factors in urban spaces but also the characteristics and attitudes of their inhabitants.